Hepcidin screening to guide iron supplementation in African children - Pasricha, S; Atkinson, S; Armitage, A; Khandwala, S; Veenemans, J; Cox, S; Eddowes, L; Hayes, T; Doherty, C; Demir, A; Tijhaar, E; Verhoef, H; et al. (SCIENCEDOMAIN International, 2015)
Objectives: Hematologic and non-hematologic benefits from iron supplementation are chiefly seen in iron deficient individuals; concerns that iron might promote infection especially in non-iron deficient individuals have complicated global anemia control policies, particularly in malaria-endemic settings. Iron homeostasis, including intestinal absorption, is controlled by hepcidin. Hepcidin is regulated by iron, erythropoietic drive, and inflammation, suggesting its potential utility to appraise iron status and thus guide iron supplementation. Methods: In 1338 African pre-school children we evaluated the Area Under the ROC Curve (AUCROC) for plasma hepcidin concentration as a diagnostic test of iron status, anemia type and erythrocyte incorporation of oral iron, determining and modeling the effects of cutoffs. Results: Hepcidin detected iron deficiency with an AUCROC = 0.85 (optimal sensitivity/ specificity at a cutoff of 5.5 ng/ml); this was not significantly affected by gender, wasting, malaria or carriage of inherited red cell disorders. In anemic children, hepcidin distinguished iron deficiency anemia from anemia of inflammation (AUCROC=0.89, optimal sensitivity/specificity cutoff 5.4 ng/ml). Hepcidin was the best predictor for >20% incorporation into erythrocytes of orally-administered 57Fe (AUCROC=0.90, optimal sensitivity/ specificity cutoff <6.9 ng/ml). If a hepcidin cutoff of 5.5 ng/ml had been used to guide iron supplementation in this population, 77% of iron deficient children would have received supplements while 80% of children with P. falciparum and 86% of children with anemia of inflammation would have avoided iron. Conclusions: In African children, hepcidin ascertains iron status, distinguishes iron deficiency anemia from anemia of inflammation, and hence could guide iron supplementation toward groups in whom it will likely be beneficial and safe.